External Tariff Liberalization in CARICOM : A Commodity-Level Analysis - Sadikov, Azim (IMF Working Papers; Working Paper ;, 2008)
This paper estimates the impact of the tariff liberalization in four largest CARICOM countries (Barbados, Guyana, Jamaica, and Trinidad and Tobago) on their trade flows. I trace changes in the product-line imports from CARICOM and non-CARICOM countries against time and commodity-level variation in external tariffs. I find that in each country the reduction of the external tariff, which eroded preferences enjoyed by member imports, increased the ratio of imports from non-member countries to imports from member countries. In Trinidad and Tobago, the higher ratio was largely the result of non-member imports crowding out member imports. In the three other countries, the ratio increased mainly because of higher non-member imports; there is little evidence that tariff reductions had an impact on member imports. Findings suggest that in Trinidad and Tobago liberalization of the external tariff reversed some of the trade diversion effects of CARICOM.